Art as a Point of Departure for Understanding Student Experience in Learning to Code. Issue 8 (August 2020) - Dahn, Maggie; Deliema, David; Enyedy, Noel
Background/Context: Computer science has been making its way into K–12 education for some time now. As computer science education has moved into learning spaces, research has focused on teaching computer science skills and principles but has not sufficiently explored the emotional aspects of students' experiences. This topic warrants further study because learning to code is a complex emotional experience marked by intense periods of success and failure. Purpose/Objective/Research Question/Focus of Study: The purpose of our study is to understand how reflecting on and making art might support students' emotional experience of learning to code. We focus our efforts on students' experiences with debugging, the process of figuring out how to fix broken code. Our research questions are: How did students reflect on their experiences and emotions in the context of art making about debugging? How did students describe the potential for making art to shape their coding practice? Setting: The setting is a two-week computer programming workshop at a non-profit organization focused on computer science education. Population/Participants/Subjects: Participants are 5th through 10th grade students attending Title I schools or with demonstrated financial need. Intervention/Program/Practice: Students participated in a visual arts class for an hour each day of the two-week workshop, in addition to three coding classes. Research Design: Design-based research anchored our study. Data sources included students' written artist statements, artifact-based interviews about artwork, and in-process conversations with the researcher-teacher leading the art class. We used a storytelling framework to make sense of how elements of our curriculum and instructional design supported student reflections on obstacles in coding, how they talked about debugging events over time, and the range of emotions they expressed feeling. Findings/Results: Findings suggest that making and reflecting on art can support students in offering descriptive accounts of learning to code and debug. Students' stories highlighted the range of ways they experienced failure in coding, the causes of those moments of failure, the flow of events through failure (what was disrupted, how the experience changed over time, and whether it was resolved), and the emotions (about emotions) that framed failure. Moreover, students described the ways that art making shaped their coding practice, including transforming how they understood themselves, set goals, relaxed after a stressful coding class, approached problem solving, and set expectations. Conclusions/Recommendations: Our results have implications for the redesign of our intervention and more broadly for the design of learning environments and computer science pedagogy.